Not sure if this is how you should do it, but it seems to make sense to me.
r(x) = (x^2 + x + 2)/(x-1)
r(x) = [(x^2 + x -2) +4]/(x-1)
r(x) = (x+2) + 4/(x-1)
Hi there,
can anyone help me with this question from my practice exam?
r(x) = (x^3 + x^2 + 2x) / x ( x - 1)
i need to write r(x) as p(x) + t(x)/q(x), for polynomials p,t and q with deg(t) < deg(q)
Thanks
Ok, sorry, I made an error in my first answer.
So here it is again, It's basically the same process but this time I won't cross out the x at the beginning:
r(x) = [x(x^2 + x + 2)]/(x^2-x)
r(x) = [x[(x^2 + x -2) +2 +2]]/(x^2-x) .... notice I added and subtracted 2 to get a factorable form
r(x) = [x(x+2)(x-1)]/[x(x-1)] + 4x/(x^2-x) ... simplify
r(x) = (x+2) + 4x/(x^2-x)
Write it out so you can see the process better.